COVID-19: Psychological Impact on Lockdown Population - Rajachandrasekar, Bhuvaneswari; Muraleedharan, K. C.; Raj, Neethu; Vaiyapuri, Sakthivel; MS, Aneena (Homœopathic Links, 2021)
Background Coronavirus disease 2019 (COVID-19) pandemic continues to surge throughout the entire world. Most of the impacted countries implemented preventive measures and lockdown to control the spread of the disease. This restriction developed psychological resilience in a wide range of the population. The objective of this study is to explore the impact on the mental health of the individuals caused by the unforeseen lockdown.Methods A cross-sectional online survey form had been designed leveraging the Google form. In the introduction section, the purpose of study and the details of the investigators were elaborately explained. The survey response was voluntary and ensured the confidentiality of the responder. The online survey consent procedures were well documented and shared with the participants. The Google forms were circulated through various social media platforms for data capturing, and the data were analysed using statistical software SPSS 23.0. A chi-squared test was performed to determine the association between demographic data and emotional data during the COVID-19 pandemic lockdown.Result A total of 2,150 responses were received out of which two of them were discarded due to insufficient data so total 2,148 responses were taken for analysis. The prevalence rate of emotional disturbance is 56.8% and 43.2% in females and males respectively (p-value = 0.001). The participant age ranges between 18 and 98 years, the mean age of participants is 33.25 years and the standard deviation is 12.24. The emotional disturbance response data are significantly associated with marital status (p-value = 0.021), socioeconomic status (p-value < 0.001), occupation (p-value = 0.019), loved one who were affected with COVID-19 (p-value = 0.034), preventive medicines taken (p-value = 0.017), sleep disturbance (p-value < 0.001), need of psychological support (p-value = 0.001), difficulty in monthly bill settlement (p-value < 0.0001), anxiouness and worry all the time during COVID-19 (p-value < 0.0001).Conclusion The survey data discovered the significant association between lockdown during COVID-19 and the emotional disturbance of the general population. These findings required additional research to identify mental health further.
Keywords: COVID-19; lockdown; psychological; emotional